Attention doesn’t slide: spatiotopic updating after eye movements instantiates a new, discrete attentional locus - Golomb, Julie D. (2011)
During natural vision, eye movements can drastically alter the retinotopic (eye-centered) coordinates of locations and objects, yet the spatiotopic (world-centered) percept remains stable. Maintaining visuospatial attention in spatiotopic coordinates requires updating of attentional representations following each eye movement. However, this updating is not instantaneous; attentional facilitation temporarily lingers at the previous retinotopic location after a saccade, a phenomenon known as the retinotopic attentional trace. At various times after a saccade, we probed attention at an intermediate location between the retinotopic and spatiotopic locations to determine whether a single locus of attentional facilitation slides progressively from the previous retinotopic location to the appropriate spatiotopic location, or whether retinotopic facilitation decays while a new, independent spatiotopic locus concurrently becomes active. Facilitation at the intermediate location was not significant at any time, suggesting that top-down attention can result in enhancement of discrete retinotopic and spatiotopic locations without passing through intermediate locations.